2022
DOI: 10.3390/jof8040395
|View full text |Cite
|
Sign up to set email alerts
|

Past, Present, and Future Perspectives on Whey as a Promising Feedstock for Bioethanol Production by Yeast

Abstract: Concerns about fossil fuel depletion and the environmental effects of greenhouse gas emissions have led to widespread fermentation-based production of bioethanol from corn starch or sugarcane. However, competition for arable land with food production has led to the extensive investigation of lignocellulosic sources and waste products of the food industry as alternative sources of fermentable sugars. In particular, whey, a lactose-rich, inexpensive byproduct of dairy production, is available in stable, high qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 192 publications
0
19
0
1
Order By: Relevance
“…Previous studies have shown that a variety of bioproducts can be obtained through the fermentation of cheese whey or WP by an assortment of fungal and bacterial species to broaden its applications. For instance, various researchers reported the production of bioethanol from these substrates using Kluyveromyces marxianus, K. lactis, Candida kefyr, and bio-engineered Escherichia coli (Koushki et al, 2012;Pasotti et al, 2017;Sampaio et al, 2020;Zou & Chang, 2022). Also, oil, volatiles, singlecell protein, and β-galactosidase have all been produced using various fungal species (Chan et al, 2018;Donzella et al, 2022;Dragone et al, 2009;Moon et al, 1978;Sampaio et al, 2020;Trigueros et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that a variety of bioproducts can be obtained through the fermentation of cheese whey or WP by an assortment of fungal and bacterial species to broaden its applications. For instance, various researchers reported the production of bioethanol from these substrates using Kluyveromyces marxianus, K. lactis, Candida kefyr, and bio-engineered Escherichia coli (Koushki et al, 2012;Pasotti et al, 2017;Sampaio et al, 2020;Zou & Chang, 2022). Also, oil, volatiles, singlecell protein, and β-galactosidase have all been produced using various fungal species (Chan et al, 2018;Donzella et al, 2022;Dragone et al, 2009;Moon et al, 1978;Sampaio et al, 2020;Trigueros et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several technologies were proposed to further valorize WP and CWP, exploiting their high lactose content to produce prebiotic oligosaccharides, carotenoids, oil, lactic acid, nanoparticles, biogas, biohydrogen and polyhydroxyalkanoate [ 3 , 6 , 9 13 ]. WP and CWP were also proposed as co-substrate additives for other fermentation processes [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…One promising technology is the use of natural or engineered microbial biocatalysts, such as bacteria [ 16 18 ] or yeasts [ 19 ], to ferment lactose into ethanol fuel. Although advances in strain performances have been proposed and examples of industrial implementation have also been reported, the dairy waste-to-ethanol conversion technology still needs improvements to guarantee its wide adoption, based on the requirements of different bioeconomic models [ 15 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alongside with the solutions to recover and valorize CW and SCW components by membrane technologies, very promising developments have been made to convert these byproducts into value-added commodities such as biofuels, bioplastics, bacterial cellulose, food colors and flavors, bioactive peptides, and single-cell proteins, as reported by several authors [12][13][14].…”
Section: Introductionmentioning
confidence: 99%